College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.8 - One-to-One Functions and their Inverses - 2.8 Exercises: 39

Answer

f and g are inverses of each other

Work Step by Step

g(f(x)) = g(3x + 4) =$ \frac{3x + 4 - 4}{3}$ = x f(g(x)) = f($\frac{x - 4}{3}$) = 3($\frac{x - 4}{3}$) + 4 = x - 4 + 4 = x Since g(f(x)) = f(g(x))
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.